2023
DOI: 10.1007/s13369-023-07968-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Study of ANFIS, ANN, and RSM and Mechanistic Modeling for Chromium(VI) Removal Using Modified Cellulose Nanocrystals–Sodium Alginate (CNC–Alg)

Abstract: The adsorption process was investigated using the ANFIS, ANN, and RSM models. The adaptive neuro-fuzzy inference system (ANFIS), artificial neural network (ANN), and response surface methodology (RSM) were used to develop an approach for assessing the Cr(VI) adsorption from wastewater using cellulose nanocrystals and sodium alginate. The adsorbent was characterized using Fourier transform infrared spectroscopy and thermogravimetric analysis. Initial pH of 6, contact time of 100 min, initial Cr(VI) concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…It was concluded that MF numbers for each inputs can affect the predictions in different ranges, and depending on the variety and data type optimum MF number could be different. In the literature, the researchers tend to use the same MF numbers for each input [ [6] , [7] , [8] , [9] , [10] , [11] , [13] , [14] , [15] , [16] ]. As we observed that in order to make good predictions these MF numbers should be optimized for each input and for each different dataset.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It was concluded that MF numbers for each inputs can affect the predictions in different ranges, and depending on the variety and data type optimum MF number could be different. In the literature, the researchers tend to use the same MF numbers for each input [ [6] , [7] , [8] , [9] , [10] , [11] , [13] , [14] , [15] , [16] ]. As we observed that in order to make good predictions these MF numbers should be optimized for each input and for each different dataset.…”
Section: Resultsmentioning
confidence: 99%
“…As seen that ANFIS configurations vary significantly among the studies, with differences in the number and type of membership functions for different input variables. Among the predictive Cr(VI) adsorption studies, Banza et al [ 14 ] and Dubey et al [ 17 ] performed the best ANFIS prediction with the lowest RMSE (0.007 and 0.038) and high R 2 (0997 and 0.99) values, however, there is no information about the used membership function and number in their studies. The adsorption data used in the study was obtained by applying response surface methodology [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations